Successful Montelukast Treatment in an Infant with Steroid-Resistant Eosinophilic Colitis - Nai-Wei Wang; Hsuan Hsieh; Yao-Jong Yang (Case Reports in Gastroenterology, 2021)
Eosinophilic colitis (EC) belongs to a group of idiopathic diseases called eosinophilic gastrointestinal disorders, which are characterized by eosinophil-predominant inflammation in the gastrointestinal tract. Corticosteroids is the first-line pharmacotherapy for EC refractory to diet therapy. We report an infant with steroid-resistant EC, who successfully returned to a healthy growth trajectory under the combined therapy of montelukast and ketotifen. An 8-month-old boy presented with bloody diarrhea, anemia, and failure to thrive (FTT) that started 6 days after birth. The patient has no known allergies. A trial of elementary diet was unsuccessful. The results of several stool cultures were unremarkable. Similarly, lower gastrointestinal series failed to identify anything significant. At 3 months of age, an esophagogastroduodenoscopy with biopsies from the distal duodenum and proximal jejunum were unremarkable. The diarrhea and FTT persisted. A rectosigmoidoscopy with biopsies was performed; the results led to the diagnosis of EC at 5 months of age. Oral prednisolone 1 mg/kg/day was prescribed; however, 3 months into the treatment, persistent bloody diarrhea and FTT were still noted. Montelukast and ketotifen were added, after which diarrhea and weight gain started to improve. Prednisolone and montelukast/ketotifen were tapered off 6 months after. He remains symptom free and has normal growth and development in a 5-year follow-up.